EDUKASI GAYA HIDUP SEHAT PADA REMAJA DI MASA COVID-19 - Safitri Safitri; Julaecha (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Adolescence is a period of human growth and development that occurs after childhood and before adulthood. The widespread spread of Covid-19 in Indonesia has an impact on all fields, especially on psychosocial and short-term and long-term mental health for children and adolescents. Disorders that occur in the form of increased food intake and decreased physical activity resulting in weight gain and obesity. The quality and impact on adolescents is determined by many factors, one of which is lifestyle. Early studies of adolescents have poor knowledge and unhealthy lifestyles such as spending time playing gadgets and sleeping late at night. Efforts that can be made in providing knowledge about healthy lifestyle for adolescents during the Covid-19 period are one of them through leaflets and online education videos. This activity was carried out on adolescents at the Baiturrahim Health Vocational School, Jambi City, as many as 32 people. The expected output target is an increase knowledge between before and after being given education. The method used is health education using leaflets and education videos that can be accessed via YouTube. Adolescent knowledge is assessed from the results of filling out a questionnaire through the google form. Monitoring and evaluation of activities using One Group Pretest and Post-test Design approaches. The result of service has increase knowledge after being given leaflets as well as online education videos to increase awareness of potential risks to their health status.